2003
DOI: 10.1002/ajmg.a.10192
|View full text |Cite
|
Sign up to set email alerts
|

US physicians' attitudes toward genetic testing for cancer susceptibility

Abstract: Genetic testing for an inherited susceptibility to cancer is an emerging technology in medical practice. Little information is currently available about physicians' attitudes toward these tests. To assess US physicians' opinions on unresolved issues surrounding genetic testing, a 15-min survey was administered to a stratified random sample of 1,251 physicians from 8 specialties, selected from a file of all licensed physicians in the US (response rate = 71.0%). Dependent measures included physicians' attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
142
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 30 publications
7
142
2
1
Order By: Relevance
“…Furthermore, although the lay public has deficient awareness of genetic testing, this is also the case with health-care providers. 30,31 As such, genomic education for health-care providers, along with the lay public, is also needed to improve the overall awareness and understanding of ASD genetic testing among both parties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the lay public has deficient awareness of genetic testing, this is also the case with health-care providers. 30,31 As such, genomic education for health-care providers, along with the lay public, is also needed to improve the overall awareness and understanding of ASD genetic testing among both parties.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] In addition, studies have also found that health-care providers have limited genomic competencies for discussing genetic testing with patients. 30,31 Accordingly, genomics education for health-care providers is needed to facilitate better genetic services.…”
Section: Discussionmentioning
confidence: 99%
“…Low perceived clinical utility, as well as concerns about potential discrimination, have repeatedly been reported as primary barriers to uptake of both traditional genetic testing and newer applications [35][36][37][38][39] . Similarly, we found that uncertain clinical utility was among the top concerns of respondents for themselves and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…SyStematic Review for cancer susceptibility, 15,17 as well as citing a lack of overall confidence in assessing patient risk. 7,23 In their assessment of 860 US PCPs, Vig et al 24 found that 38.3% were uncomfortable with making screening and prevention recommendations and were uncertain about which patients are medically appropriate to refer.…”
Section: Genetics In Medicine | Volume 17 | Number 3 | March 2015mentioning
confidence: 99%
“…35,36 The second most common ELSI barrier (n = 15 citations in 15/38 studies) was the fear of social or insurance discrimination for their patients as a result of their genetic information. 37 Freedman et al 17 found that more than 80% of 1,251 US PCPs surveyed thought that patients with positive genetic testing results were at risk for insurance discrimination. Another survey identified 70% of PCPs with this concern.…”
Section: Genetics In Medicine | Volume 17 | Number 3 | March 2015mentioning
confidence: 99%